Policy Of A Merit System To Make A Good And Clean Government In The Middle Of Bureaucratic Politicization - Yahya Pandega Putra; Eko Priyo Purnomo; Suswanta Suswanta; Aulia Nur Kasiwi (Journal of Government and Civil Society, 2020)
The phenomenon of the politicization of the bureaucracy is nothing new in politics in Indonesia, the politicization of the bureaucracy has long been the case ever since the implementation of the general elections in Indonesia for the first time in 1955. The entire regime that once ruled in Indonesia has ever put through the politicization of this bureaucracy even up regime power today because by utilizing the existing positions in the bureaucracy, it can pave the way for political purposes. The application of the merit system policies to achieve good governance and clean is a step taken by the Government as a system of monitoring the implementation of transfer, promotion, and demotion conducted by political officials. This study uses qualitative research using reference data from many previous studies used as a literature review and a national online media news concerning the application of the merit system and bureaucracy politicization pressure that occurs. Based on the analysis using the software NVivo 12 Plus, it can be deduced that to realize good and clean government in the middle of bureaucratic politicization needed policy on the application of the merit system in personnel management, which aims to encourage the government bureaucracy to become more competent in solving the problems of public-oriented towards public service.Fenomena politisasi birokrasi bukanlah hal baru dalam politik di Indonesia, politisasi birokrasi telah lama terjadi sejak penyelenggaraan pemilihan umum di Indonesia pertama kali pada tahun 1955. Seluruh rezim yang pernah berkuasa di Politisasi birokrasi ini pernah dilakukan Indonesia bahkan sampai kekuasaan rezim saat ini karena dengan memanfaatkan posisi yang ada di birokrasi dapat membuka jalan bagi kepentingan politik. Penerapan kebijakan merit system untuk mewujudkan good governance dan clean merupakan langkah yang diambil oleh Pemerintah sebagai sistem pengawasan terhadap pelaksanaan mutasi, promosi, dan penurunan pangkat yang dilakukan oleh pejabat politik. Penelitian ini menggunakan penelitian kualitatif dengan menggunakan data referensi dari berbagai penelitian sebelumnya yang digunakan sebagai tinjauan pustaka dan pemberitaan media online nasional mengenai penerapan sistem merit dan tekanan politisasi birokrasi yang terjadi. Berdasarkan analisis dengan menggunakan software NVivo 12 Plus, dapat disimpulkan bahwa untuk mewujudkan pemerintahan yang baik dan bersih di tengah politisasi birokrasi diperlukan kebijakan penerapan merit system dalam pengelolaan kepegawaian, yang bertujuan untuk mendorong agar birokrasi pemerintahan menjadi lebih kompeten dalam menyelesaikan masalah-masalah yang berorientasi pada publik menuju pelayanan publik.